Sebaran dan Pola Wisata Alternatif Menggunakan Pendekatan Spasial di Kota Kendari - Hasanah, Nur; Irsan, Laode Muhamad (Journal of Geographical Sciences and Education, 2025)
Kendari City has diverse tourism potential but its development is still focused on the main destinations and has not presented the diversity of alternative tourism potential available so that strategic efforts are needed. This study aims to identify and map the distribution and pattern of alternative tourism locations in Kendari City. This study was conducted at several points in Kendari City. This study is a survey study with a spatial approach based on geographic information systems and using Average Nearest Neighbor (ANN) to determine the distribution pattern of tourist locations. The results of this study are: 1) The distribution of alternative tourism in Kendari City is spread across 19 locations in the sub-districts of Poasia, Kambu, Kadia, Mandonga, Kendari Barat and Baruga. The distribution of this location is divided into 4 classifications, namely agrotourism, cultural tourism, health and spiritual; and 2) the distribution pattern of alternative tourism forms a random pattern, which is tourist locations are not concentrated in one location only.